Enzymatic activity of hypopharyngeal gland extractsfrom workers of Apis mellifera (Hymenoptera, Apidae, Apinae) - Costa, RAC; da Cruz-Landim, C. (California State University, 2002)
This research presents a comparative study of enzymatic activity of the hypopharyngeal gland extracts from workers of Apis mellifera in three physiologic stages: newly emerged, nurse and forager workers, with the objective of contributing to the comprehension of the gland function. In order to determinate the enzymes present in the extracts, the Api Zym kit (Bio Merieux) was used to test the activity of 19 different enzymes. The enzymes found in larger amounts only in the hypopharyngeal glands from certain individuals were the following: in newly emerged workers, the N-acetyl-double down arrow-glucosaminidase that may be digesting the chitin of some food ingested by the bee; in forager workers, the acid phosphatase that is likely acting in authophagic processes, the a-glucosidase, in the processing of nectar into honey, and the double down arrow-glucosidases, in the pollen digestion.
Keywords: hypopharyngeal glands; workers; bees; honeybee; Apoidea; royal jelly; enzymes; glucosidase; acid phosphatase